2018
DOI: 10.15520/ijnd.2018.vol8.iss03.2050.01-10
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes and Practices in Relation to Cervical Cancer Screening among Female Employees at King Abdulaziz University

Abstract: Background: Cervical cancer ranks as the fourth most frequent cancer among women and the second most common female cancer in the women aged 15 to 44 years in world. In Saudi Arabia, there is a population of 2,784 million women aged 15 years and older who are at risk of developing cervical cancer. Current estimates in Saudi Arabia indicate that every year, 241 women are diagnosed with cervical cancer and 84 die from the disease. Aim: The aim of this study is to assess the knowledge, attitudes and practices in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…A great deal of knowledge, attitude, and practice (KAP) studies regarding cervical cancer have been conducted among various populations in various geographical settings in Saudi Arabia, and shockingly, some of the studies reported poor knowledge and awareness even among teachers, well-educated employees, and health workers [12,[16][17][18]. Most of these studies were conducted among the general female population.…”
Section: Introductionmentioning
confidence: 99%
“…A great deal of knowledge, attitude, and practice (KAP) studies regarding cervical cancer have been conducted among various populations in various geographical settings in Saudi Arabia, and shockingly, some of the studies reported poor knowledge and awareness even among teachers, well-educated employees, and health workers [12,[16][17][18]. Most of these studies were conducted among the general female population.…”
Section: Introductionmentioning
confidence: 99%